Critical theory in the twenty-first century - Schecter, Darrow (New York : Bloomsbury Academic, 2013)
'Critical Theory in the Twenty-First Century provides a thorough overview of critical theory, looking at its history and shortfalls. First, the book explains the developments from the Frankfurt School and from more recent schools of thought, including Derrida, Deleuze, deconstruction, and post-structuralism. Then it looks at how critical theory has not kept pace with the changes and conflicts brought on by the post-Cold War world and globalization and how its deficits can be addressed. For the author, more than ever critical theory needs to synthesize theoretical perspective and empirical research. It also needs to be reconfigured in the light of the demands of new social movements, post-colonialism, and globalization. This volume is part of Critical Theory and Contemporary Society, a series that uses critical theory to explore contemporary society as a complex phenomenon and includes works on democracy, social movements, and terrorism. A unique resource, Critical Theory in the Twenty First Century will interest anyone researching issues in political theory, international relations theory, social theory, and critical theory.'--Publisher's website.
Introduction -- Dialectics, De-Naturalisation and Social Differentiation (I): From the Public Sphere to the Emergence of Civil Society -- Dialectics, De-Naturalisation and Social Differentiation (II): From the Cognitive Content of Aesthetics to Critical Theory -- Critical Theory and Mediated Non-Identity -- Critical Theory and Political Theory -- New Paths Beyond the Marx-Freud Synthesis -- Conclusion: The Mediations of Society.
Includes bibliographical references and index.
Keywords: Civil society; Differentiation (Sociology).; Political science